2021
DOI: 10.1039/d1tc03600a
|View full text |Cite
|
Sign up to set email alerts
|

Design of biodegradable and biocompatible conjugated polymers for bioelectronics

Abstract: The emerging field of bioelectronics leverages the optoelectronic properties of synthetic materials to interface with living systems. The convergence of modern electronics with biology has offered lifesaving medical treatments, with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 105 publications
0
72
0
Order By: Relevance
“…They have attracted especially high interest in recent years due to the significant developments in the synthetic approaches and desired applications [ 2 , 3 , 4 ]. Taking into account the favorable processability of conductive polymers, possibility of tailoring their structures and functions at the molecular scale, low production costs, and reasonable stability, π-conjugated polymers may find applications in next-generation electronic devices [ 5 ], such as photovoltaic organic solar cells [ 6 ], bioelectronics [ 7 ], energy storage devices [ 8 ], energy conversion systems [ 9 ], and electrochemical transistors [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…They have attracted especially high interest in recent years due to the significant developments in the synthetic approaches and desired applications [ 2 , 3 , 4 ]. Taking into account the favorable processability of conductive polymers, possibility of tailoring their structures and functions at the molecular scale, low production costs, and reasonable stability, π-conjugated polymers may find applications in next-generation electronic devices [ 5 ], such as photovoltaic organic solar cells [ 6 ], bioelectronics [ 7 ], energy storage devices [ 8 ], energy conversion systems [ 9 ], and electrochemical transistors [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conductive polymers continue to be an active research topic for biomaterials and have demonstrated record tensile strains (>100%), low moduli (kPa-MPa), and conductivity (10 1 -10 4 S m -1 ), [578][579][580][581][582] among other tunable charac teristics such as anisotropy, [583] adhesiveness, [156,[584][585][586] and bio degradability. [587] A wide range of polymers are being explored as stretchable semiconductors, optimizing for charge car rier mobility, [587][588][589] device density, [590] ionic transport, [591] and neuromorphic computing.…”
Section: Other Conductorsmentioning
confidence: 99%
“…15 Second, it further solidifies the position of organic electronics as less toxic, more environmentally friendly, and more sustainable than their inorganic counterparts. [16][17][18] Furthermore, DArP appeals for its atom economy, effectiveness (providing targets in fewer synthetic steps), generation of more benign byproducts, and decrease of the overall cost for the preparation of conjugated polymers.…”
Section: Introductionmentioning
confidence: 99%